PEMBERIAN VAKSIN SINOVAC KEPADA MASYARAKAT UNTUK MENCEGAH PENYEBARAN COVID 19 - Layla Imroatu Zulaikha (Universsitas Mitra Indonesia, 2021)
To suppress the increasing number of cases, the COVID-19 vaccine has been administered. The government also recommends that everyone get it. Vaccination or immunization aims to make a person's immune system able to recognize and quickly fight bacteria or viruses that cause infection. The goal to be achieved by giving the COVID-19 vaccine is to reduce morbidity and mortality due to this virus. Although not 100% able to protect a person from Corona virus infection, this vaccine can reduce the possibility of severe symptoms and complications due to COVID-19. This Community Service (PkM) aims to increase public awareness to vaccinate, as well as provide education to the public on the importance of giving vaccines to prevent the transmission of covid 19. In addition, the benefits of giving vaccines are not only for ourselves, but also for the people around us. who do not have a good immune system.The activity of providing free vaccines to the community is very important, the COVID-19 vaccine is expected to be a solution to end the pandemic that has claimed many lives and paralyzed community activities, and your participation in this vaccination program will greatly help the recovery of our country's condition.Keywords: Vaccines, Herd Immunity, Covid-19